Design and evaluation of in vivo bioavailability in beagle dogs of bilayer tablet consisting of immediate release nanosuspension and sustained release layers of rebamipide - Jin, Gang; Ngo, Hai V.; Wang, Jie; Cui, Jing Hao; Cao, Qing Ri; Park, Chulhun; Jung, Minji; Lee, Beom Jin (International Journal of Pharmaceutics, 2022)
The purpose of this study was to develop a once-daily, bilayer matrix tablet with immediate (IR) and sustained release (SR) layers of poorly water-soluble and absorption site dependent rebamipide (RBM) to substitute three times a day IR tablet. Owing to the pH-dependent poor water solubility of RBM in low pH condition, salt-caged nanosuspensions (NSPs) consisting of RBM and poloxamer 407 (POX 407) or poloxamer 188 (POX 188) were prepared using an acid-base neutralization method to increase the dissolution rate, which was subsequently applied to the immediate-release (IR) layer. Polyethylene oxide (PEO) with different molecular weights (PEO 100,000 and PEO 5,000,000) and hydroxypropyl methylcellulose 4000 (HPMC 4000) were then investigated as SR agents to incorporate into the SR layer with pure RBM via wet granulation method. The dissolution profile of the optimized bilayer tablet having 50% IR and 50% SR layer of 300 mg RBM showed that the IR layer could rapidly disintegrate in pH 1.2 buffer solution within 2 h, reaching 50% of drug release from the tablet, followed by an extended drug release from the SR layer in pH 6.8 buffer over 24 h. An in vivo pharmacokinetic study was carried out in beagle dogs to compare the optimal formulation (300 mg RBM bilayer tablet) and the commercial tablet (Mucosta® 100 mg) as a reference. Unexpectedly, despite enhanced dissolution rate in a controlled manner, a designed bilayer tablet had no dose- and dosage form dependent in vivo bioavailability in beagle dogs as compared with IR 100 mg RBM reference tablet. It was evident that solubility in low pH condition, gastric residence time and absorption site of RBM should be carefully considered for designing specific SR or gastroretentive dosage form to improve therapeutic outcomes.
Keywords: Alanine; Animals; Biological Availability; Delayed-Action Preparations; Dogs; Poloxamer; Quinolones; Solubility; Tablets; Water; Absorption site dependency; Bilayer tablet; Immediate and sustained release; Inconsistency of in vivo bioavailability; Poorly water-soluble rebamipide